Responding to Youth Crime in Canada - Doob, Anthony N., 1943- (Book collections on Project MUSE., 2004)
"The authors describe what is known about Canadian youth crime, and the operation of the youth justice system in the context of the changes in the law that are taking place. The authors posit that the youth justice system has a relatively modest impact on youth crime. In order to respond intelligently to it and to evaluate the response of the state, two sets of information must be understood. First, society must try to understand what 'youth crime' looks like in Canada. Second, in order to understand ₁ and evaluate ₁ the changes that are being made in youth justice legislation in Canada, a clear understanding of the manner in which the youth justice system currently operates is necessary."